The Implementation of Rock Paper Scissors Game for Teaching Speaking at Indocita Foundation Malang - Annisaus Shofia Bella; Trisnian Ifianti (Verba: Journal of Applied Linguistics, 2022)
This  study  aimed  to  describe  the  implementation  of  rock  paper  scissorss game  in  teaching  speaking  at  Indocita  Foundation  Malang.  English  is  the  most prime language in the world. Speaking is the core of language learning also one of the most important skills in English to be developed and enchanced as means of effective communication. The approch used descriptive qualitative method where 35 students of junior high school especially nineth grade at Indocita Foundation Malang participated. The data collection used observation, interview and questionnaire. The result showed that  the implementation of rock paper scissors game helped the students to motivate  or treat the students to produce the  voice immediately.  Rock  paper  scissors  game  also  could  motivate  the  students’  to  be brave to speak up in English speaking class. This game in teaching speaking made the students realized that the students might have compete  with other members’ group and the students  got  more  effort  to  be  the  winner  in finishing  the  game soon.  The rock paper scissors took the students attention with the colourful papers in front of them which the students touched while students were speaking up. The problems were faced by the students during the process of implementation of rock paper scissors game in teaching speaking at Indocita Foundation Malang such as 1) cooperation  with  the  member’s  of  the  group  2)  lack  of  vocabularies  3)  lack  of fluency.